PENGARUH TAMBAHAN HERBAL (JAHE, KUNYIT, DAUN SALAM) DAN PENCAHAYAAN TERHADAP KOLESTROL DARAH DAN LEMAK ABDOMINAL BROILER - Mei Sulistyoningsih; Reni Rakhamawati; Ardiansah Ardiansah (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2018)
The purpose of this study was to determine the effect of additional ginger, bay leaf, and turmeric in rations and lighting treatment against blood cholesterol and abdominal fat broiler. Subjects used in the study were 100 DOC unsex. The design used in this research is Randomized Complete Random (RAL) with 3 x 2 factorial pattern with Factor A of herbal medicine 3 levels of sedangkn factor B of lighting treatment for 2 levels with 4 replications, each replication there are 4-5 broiler chickens. The treatments in this study were JC1: commercial feed + 2% ginger + light 1L: 3D, JC2: commercial ration feed + 2% ginger + light 1L: 2D, SC1: commercial feed + 3% bay leaves + 1L light: 3D , SC2: commercial ration feed + 3% bay leaves + light 1L: 2D, KC1: commercial ration feed + 0.2% turmeric + light 1L: 3D, KC2: commercial ration feed + 0.2% turmeric + light 1L: 2D . The research variables studied were blood cholesterol and abdominal fat. The data obtained were analyzed by using ANOVA with 5% level, the result showed no significant effect (P> 0,05) on the treatment of blood cholesterol and abdominal fat of broiler chicken. It can be concluded that the administration of ginger, bay leaf, and turmeric in ration and lighting treatment does not affect blood cholesterol levels and abdominal fat of broiler chickensÂ